2018
DOI: 10.1038/s41467-018-05050-6
|View full text |Cite
|
Sign up to set email alerts
|

A window of opportunity for cooperativity in the T Cell Receptor

Abstract: The T-cell antigen receptor (TCR) is pre-organised in oligomers, known as nanoclusters. Nanoclusters could provide a framework for inter-TCR cooperativity upon peptide antigen-major histocompatibility complex (pMHC) binding. Here we have used soluble pMHC oligomers in search for cooperativity effects along the plasma membrane plane. We find that initial binding events favour subsequent pMHC binding to additional TCRs, during a narrow temporal window. This behaviour can be explained by a 3-state model of TCR tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 45 publications
(52 reference statements)
7
28
0
Order By: Relevance
“…Together these results showed that the time point of affinity measurement is important, allowing for clear indication of TCR affinity modulation around 5 minutes after initiation of immune synapse formation. The model accords experimental findings, which suggest that peak cooperativity is achieved 4-8 minutes after the first observed binding event [12].…”
Section: Affinity Dynamics Depend On the Time Of Measurementsupporting
confidence: 87%
See 1 more Smart Citation
“…Together these results showed that the time point of affinity measurement is important, allowing for clear indication of TCR affinity modulation around 5 minutes after initiation of immune synapse formation. The model accords experimental findings, which suggest that peak cooperativity is achieved 4-8 minutes after the first observed binding event [12].…”
Section: Affinity Dynamics Depend On the Time Of Measurementsupporting
confidence: 87%
“…This has been interpreted as cooperativity between TCRs to boost their affinity toward pMHC, during the accumulation of TCR-pMHC complexes [11]. This behavior was shown to operate on a narrow time window, where the initial TCR-pMHC ligations favor further binding events [12]. Pielak et al [11] demonstrated that the dwell time, τoff, and consequently the dissociation rate, koff, of individual TCR-pMHC complexes remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…In EM, TCR nanoclusters were defined as gold particle aggregates at less than 10 nm distance from one another. Previous analyses showed that this criterion permits identification of TCR nanoclusters formed by TCR-TCR interactions (Kumar et al, 2011); these tightly-associated TCR nanoclusters would allow inter-TCR cooperativity for pMHC binding (Martín-Blanco et al, 2018). We therefore intentionally considered TCR not to be in the same nanocluster if the gap between them was >10 nm; this excludes considering more loosely associated TCR as nanoclusters, but the strict definition allowed association of TCR nanoclusters to a T cell biological function.…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity gradient (memory>>effector>naïve) in CD8 + T cells is linked to increased valency of preformed TCR oligomers at the cell surface, termed TCR nanoclusters (Kumar et al, 2011). This antigenindependent TCR nanoclustering (Lillemeier et al, 2010, Schamel & Alarcon, 2013, Schamel et al, 2005, Schamel et al, 2006, Sherman et al, 2011 enhances antigenic sensitivity by increasing avidity to multimeric peptide-major histocompatibility complexes (Kumar et al, 2011, Molnar et al, 2012 and by allowing cooperativity between TCR molecules (Martín-Blanco et al, 2018, Martínez-Martín et al, 2009. TCRβ subunit interaction with cholesterol (Chol) and the presence of sphingomyelins (SM) are both essential for TCR nanoclustering (Beck-Garcia et al, 2015, Molnar et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A cell tracking experiment by Halle et al showed cooperativity, in which cell killing is a steep function of the number of T-cell contacts with the target cell with Hill coefficients exceeding 7 (46,47). One basis for such cooperativity is evidence that that T-cell receptors (TCRs) work cooperatively in the same T-cell, so that TCR activity spreads in a TCR nanocluster (48).…”
Section: Ashm Requires Cytotoxic T-cells To Differentially Remove Celmentioning
confidence: 99%